DEXMEDETOMIDINE ALONE OR WITH KETAMINE IN ADDITION TO ROUTINE FENTANYL ADMINISTRATION IN POST CARDIAC SURGERY PATIENTS: A RANDOMIZED CONTROLLED TRIAL - Ali Rai, Shumaila; Furqan, Aamir; Khan, Muhammad Imran; Kaneez Um e farwa; Adnan, Ahmed; Afzal, Dr Waseema (Journal of Postgraduate Medical Institute, 2022)
Objective: To compare the effects of dexmedetomidine alone (DA) with dexmedetomidine plus ketamine (KD) combination in addition to routine fentanyl administration in post-cardiac surgery patients Methodology: The trial was conducted at the Department of Anaesthesia and Critical Care, Chaudhary Pervaiz Elahi Institute of Cardiology Multan, from July 2020 to December 2020. A total of 40 patients planned for elective coronary artery bypass grafting (CABG) were randomized by lottery method for dexmedetomidine alone (Group DA, n=20) or dexmedetomidine plus Ketamine (Group KD, n=20) to maintain Ramsay sedation score > 4 during assistedventilation. All patients received fentanyl for postoperative analgesia. The mean arterial blood pressure, heart rate, sedation score, pain score, and mean extubation time were compared between two groups and analyzed by using SPSS version 23. Results: Total fentanyl dose was 45.65 ± 8.23 microgram in group KD and 146.01 ± 14.18 microgram in group DA (p = 0.001). The time of weaning was 344.65 ± 43.89 minutes and 446.60 ± 73.75 minutes in groups KD and DA, respectively (p = 0.001). The time of Extubation was 389.90 ± 35.89 minutes and 535.30 ± 36.25 minutes in groups KD and DA, respectively (p <0.001). The ICU stay, heart rate, mean arterial pressure, Ramsay score, and non-verbal Pain score was comparable in both study groups (p>0.05). Conclusion: Utilizing Ketamine plus dexmedetomidine for sedation post-Coronary Artery Bypass Graft (CABG) procedure gave a brief term of mechanical ventilation and early extubation with less fentanyl requirement than dexmedetomidine alone. Hemodynamic stability was present in both groups.